Adrian Piper - a reader - Costello, Diarmuid; Costello, Diarmuid; Hall, Emily ca. 20. Jh (Museum of Modern Art, 2018)
"Published for MoMA's retrospective exhibition and in collaboration with the artist, this volume presents new critical essays that expand on Piper's practice in ways that have been previously under- or unaddressed. Focused texts by established and emerging scholars assess themes in Piper's work such as the Kantian framework that draws on her extensive philosophical studies; her unique contribution to first-generation conceptual art; the turning point in her work, in the early 1970s, from conceptual works to performance; the connection of her work with her yoga practice; her ongoing exposure of and challenge to xenophobia and sexism; and the relation between prevailing interpretations of her work and the viewers who engender them"
Impressum: "Published in conjunction with the exhibition Adrian Piper: a synthesis of intuitions, 1965-2016 at the Museum of Modern Art, New York, March 31-July 22, 2018"
Keywords: Piper, Adrian -- 1948-; Piper, Adrian / 1948- / Criticism and interpretation; ART / General; Ausstellungskatalog -- Museum of Modern Art -- 31.03.2018-22.07.2018 -- New York, NY; Aufsatzsammlung